2017
DOI: 10.1038/mp.2016.243
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 protects the brain during inflammatory conditions

Abstract: Sepsis is a prevalent health issue that can lead to central nervous system (CNS) inflammation with long-term behavioral and cognitive alterations. Using unbiased proteomic profiling of over 100 different cytokines, we found that Lipocalin-2 (LCN2) was the most substantially elevated protein in the CNS after peripheral administration of lipopolysaccharide (LPS). To determine whether the high level of LCN2 in the CNS is protective or deleterious, we challenged Lcn2−/− mice with peripheral LPS and determined effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 46 publications
3
127
0
Order By: Relevance
“…These include C4b , a complement component and marker of astrocyte activation and aging (Boisvert et al, 2018; Clarke et al, 2018), Megf10 , which mediates astrocytic synapse elimination (Chung et al, 2013), and Pla2g3 , a phospholipase implicated in ROS-induced neuronal damage (Martínez-García et al, 2010). Activation marker Lcn2 (lipocalin 2), an anti-inflammatory mediator in the brain (Kang et al, 2018), was not increased, again suggesting a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 96%
“…These include C4b , a complement component and marker of astrocyte activation and aging (Boisvert et al, 2018; Clarke et al, 2018), Megf10 , which mediates astrocytic synapse elimination (Chung et al, 2013), and Pla2g3 , a phospholipase implicated in ROS-induced neuronal damage (Martínez-García et al, 2010). Activation marker Lcn2 (lipocalin 2), an anti-inflammatory mediator in the brain (Kang et al, 2018), was not increased, again suggesting a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that after LPS stimulation, Lcn2 as an acute phase protein is rapidly induced in various cells of the central nervous system, including astrocytes, microglia and endothelial cells [31-33]. Moreover, the expression of LCN2 was found to be markedly elevated in the brain and in cultured astrocytes at 4–8 h after exposure to an inflammatory stimulus [19, 34, 35]. Similar to these studies, we found that LCN2 protein levels in retinal tissues and in cultured Müller cells were significantly increased at 8 h after LPS treatment, suggesting that LCN2 is likely to be involved in the early response to inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that LCN2 plays various biological roles in cell survival, apoptosis and iron transport [36]. Previous studies have shown that LCN2 is an important mediator in the regulation of a range of inflammatory diseases, including sepsis, inflammatory bowel disease, and in inflammatory disorders of the central nervous system [19, 37, 38]. However, the specific roles of LCN2 in different inflammatory conditions are not always consistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations